Suprachoroidal Versus Intravitreal Injection of Triamcinolone Acetonide As Primary Treatment For Diabetic Macular Edema - Fatima Shafqat Khan; Asfandyar Asghar; Brig Rana Intisar-ul-haq; Tehmina Nazir; Naila Obaid; Munazza Aslam (Journal of Rawalpindi Medical College)
Objective: This study aims to evaluate and compare the effects of suprachoroidal and intravitreal triamcinolone administration, as a primary treatment, on best corrected visual acuity (BCVA), central macular thickness (CMT), and intraocular pressure (IOP) in patients with diabetic macular edema (DME).